RELEVANSI PEMBELAJARAN BERDIFERENSIASI DENGAN PENDIDIKAN JIWA PERSPEKTIF IBNU SINA - Balqisa Ratu Nata; Annisa Rahmania Azis; Nazila Mumtaza Zamhariroh; Mohammad Salik; Muhammad Fahmi (STAI Pelabuhan Ratu, 2024)
This article discusses the relevance between the concept of differentiated learning and the concept of soul education from Ibn Sina's perspective. Ibn Sina emphasized the importance of paying attention to the development of the soul, talents, and unique character of each individual in the education process. This study aims to explore how Ibn Sina's soul education theory can provide a strong philosophical foundation for the implementation of differentiated learning. This study uses a qualitative method with a literature study research approach. The results of the study indicate that Ibn Sina's concept of soul education is in line with the concept of differentiated learning in the independent curriculum, where each student cannot be treated the same, but must be adjusted to the development of age, soul, physical, intellectual, and moral. According to Ibn Sina, every human being is seen as an individual who has unique and different potential. Therefore, education should ideally pay attention to the needs and development of a person's soul specifically according to the development of the child's age. The implication of this study is for educators to adjust learning methods to the emotional, intellectual, and spiritual needs of students, so that they become more personal and effective.